Development of experimental samples of functional soft drinks and evaluation of organoleptic and physicochemical indicators - A. A. Skhalyakhov; K. R. Siyukhov; Z. T. Tazova; N. T. Siyukhova (Новые технологии, 2021)
Development of innovative activities in the Russian Federation implicates the creation of safe and, at the same time, full-fledged in composition and consumer properties of specialized food products, as one of the main and promising tasks of the food industry. This is due to the need to provide a modern person’s diet with necessary nutrients and prevention of nutritional diseases. In this regard, development of recipes and production of functional food products using biologically active components of non-traditional plant raw materials growing in the Republic of Adygea and conducting scientific research, including the assessment of quality and biological value, are relevant. The aim of the research is to determine organoleptic, physicochemical parameters and functional properties of experimental samples of soft drinks using extracts from compositions of plant raw materials. During the course of performance phytocomposition models of mixtures of adaptogenic and antioxidant action and for the prevention of iodine deficiency have been developed, the optimal extraction option has been selected, laboratory experimental samples of functional soft drinks have been designed, quality indicators and functional properties have been investigated. The results of studying organoleptic indicators prove that the taste in all samples is quite harmonious and pleasant, with characteristic light herbal tones, the color of drinks ranges from light to rich amber, depending on the composition. The average indicator of antioxidant activity fluctuates between 156 to 244 mg/dm3. Functional food ingredients content (potassium, vitamins C, E, flavonoids and iodine trace element) of experimental samples of functional soft drinks comply with GOST R 56543-2015 Functional drinks. General technical conditions [1] are suitable for systematic consumption in order to improve physiological functions in the human body.